Associations between sarcopenia and domains of quality of life in older adults: a population-based cross-sectional study - Emma C. West; Lana J. Williams; Jessica A. Davis; Julie A. Pasco (Health and Quality of Life Outcomes)
Abstract Background Sarcopenia is an age-related skeletal muscle disorder associated with deleterious health outcomes. Few studies have examined associations between sarcopenia and quality of life (QoL). Therefore, the purpose of this study was to determine whether sarcopenia is independently associated with specific domains of QoL. Methods This cross-sectional study examined associations between sarcopenia and domains of QoL in a population-based sample of 682 adults aged 60–96 years. Sarcopenia was defined according to the revised European Working Group on Sarcopenia in Older People algorithm. Appendicular lean mass was assessed using dual-energy Xray absorptiometry, handgrip strength by dynamometry, and physical performance using the Timed UupandGo test. The World Health Organisation’s abbreviated QoL tool was used to assess QoL across four domains: physical health, psychological, social relationships and environment. Multivariable logistic regression was used to investigate associations between sarcopenia and poor QoL. Results After adjusting for potential covariates, sarcopenia (either probable or confirmed) was associated with an increased likelihood for poor physical health-related QoL [OR 2.77 (95% CI 1.31–5.88)] and poor psychological-related QoL [OR 2.69 (95% CI 1.41–5.15)]. No associations were detected between sarcopenia and the social relationships or environment domains. Conclusions These findings highlight the importance of maintaining skeletal muscle health in older age. Interventions to prevent or manage sarcopenia among older adults may contribute to better QoL for this population and warrant further investigation.